A study of the professional image of the department of physiotherapy at the Tygerberg hospital complex - E. Mouton (AOSIS, 1983)
In this study the professional image of the Department of Physiotherapy as observed by physicians, physiotherapists, paramedical staff and laymen (patients) was looked at. The Nominal Group Technique (N.G.T.) was used to develop the Semantic Differential (S.D.) which was used as the criterion of measurement. In the results, the afore-mentioned groups indicated a positive image of the Department of Physiotherapy and there seems to be a minimal difference in image observation amongst the different groups.